Clinical characteristics of patients with takotsubo syndrome recurrence: An observational study with long-term follow-up. (15th April 2021) - Arcari, Luca; Cacciotti, Luca; Limite, Luca Rosario; Russo, Domitilla; Sclafani, Matteo; Semeraro, Raffaella; Ansalone, Gerardo; Volpe, Massimo; Autore, Camillo; Musumeci, Maria Beatrice
Abstract: Background: Research investigating takotsubo syndrome (TTS) recurrence yielded conflicting results. Aim of the present study is to describe clinical characteristics of patients with TTS recurrence in a cohort with available long-term follow-up. Methods: The study population included 234 TTS patients enrolled in a prospective multicenter registry, median follow-up of 1328 (407, 2526) days. To investigate factors associated with TTS recurrence, we analyzed patients with recurrence (Group A) in comparison with a subgroup of TTS patients within the whole population (group B) who had similar age, sex and median follow-up length (Group A 2280 days vs Group B 2361 days). Results: We observed 9 TTS recurrences affecting 8 patients, all women, with a rate of 0.9% patients/year. Median time to first recurrence was 1593 days (interquartile range: 950, 2516). We detected no significant differences between patients with and without recurrences regarding cardiovascular risk factors, symptoms, ECG and echocardiographic findings at presentation, discharge therapy. Physical trigger and chronic obstructive pulmonary disease (COPD) were more prevalent in patients who experienced a recurrence (75% vs 27% and 50% vs 14% with p = 0.01 and p = 0.022 respectively). Univariable Cox regression analysis identified physical trigger and history of COPD to be both associated with TTS recurrence [hazard ratio (HR) 11.4, 95% confidence interval (CI) 2.29–56.8, p = 0.003 and HR 4.94, 95% CI 1.16–20.99 p = 0.031 respectively]. Conclusion: TTS recurrence is relatively uncommon. Association with physical trigger and COPD would suggest a closer follow-up in this subgroup of patients. Highlights: Patients with takotsubo syndrome (TTS) can develop a recurrence after first event. We observed a TTS recurrence rate of 0.9% patients/year. TTS recurrence can occur even several years after first episode. Associated factors included history of COPD and physical trigger at first event.